Perlindungan Hukum terhadap warga negara Indonesia yang bekerja di negara asing yang terkena penjatuhan hukuman mati berdasarkan Peraturan Perundang-undangan di Indonesia - azahra, sakila nur; Ratna, Yulvita (Lex Librum : Jurnal Ilmu Hukum, 2025)
TKI is an abbreviation of Indonesian Migrant Workers.  The title of TKI is given to those who are Indonesian citizens who work abroad.  One person becomes a migrant worker due to the high level of poverty and unemployment in Indonesia and the difficulty of finding jobs in Indonesia.  So that TKI choose to look for work abroad to get a higher income, but on the other hand Indonesian Migrant Workers (TKI) abroad get discriminatory actions by their employers, therefore before working abroad TKI must choose an official PJTKI institution so that  if there is a death penalty case against TKI The government needs legal protection for TKI.  In carrying out its duties and responsibilities to improve efforts to protect Indonesian Migrant Workers abroad who are subject to the death penalty, the Government is obliged to: 1) ensure the fulfillment of the rights of prospective TKI, both those who depart through the executor of the placement of TKI, and those who depart independently, 2) supervise the implementation of the placement.  prospective TKI, 3) establish and develop an information system for the placement of prospective TKI abroad, 4) carry out diplomatic efforts to guarantee the fulfillment of the rights and protection of TKI optimally in the destination country, and 5) provide protection to TKI during the period prior to departure, placement and retirement.  placement (Articles 5 to 7).  So the government must guarantee the rights of all citizens.  In collecting data, this article uses a juridical-normative research method.  This juridical-normative method uses research methods obtained based on library sources in order to obtain results from researching library materials or only secondary materials